2009
DOI: 10.1086/597177
|View full text |Cite
|
Sign up to set email alerts
|

Civil Liberty in America: The Diffusion of Municipal Bill of Rights Resolutions after the Passage of the USA PATRIOT Act

Abstract: In the years since the 9/11 terrorist attacks, some 400 local governments passed "Bill of Rights" resolutions in opposition to the USA PATRIOT Act. Event history analyses show that cities with progressive profiles were markedly quicker to pass such resolutions. These effects are strongest in the early phase of the Bill of Rights campaign, a period for which there is also robust evidence of contagious influence among nearby cities. The authors argue that the campaign's success lies in the miscibility of multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…Living wage ordinances were adopted by 7% of these cities over a 12-year period (1994-2006). A crucial difference between the two issues is that municipal-level ordinances to protect individual rights were largely symbolic-as laws, they carry little weight, as federal law preempts state and local law (Vasi and Strang 2009). In contrast, raising wages even for a small percentage of city workers is a redistributive issue with an immediate cost to some businesses.…”
Section: Resultsmentioning
confidence: 99%
“…Living wage ordinances were adopted by 7% of these cities over a 12-year period (1994-2006). A crucial difference between the two issues is that municipal-level ordinances to protect individual rights were largely symbolic-as laws, they carry little weight, as federal law preempts state and local law (Vasi and Strang 2009). In contrast, raising wages even for a small percentage of city workers is a redistributive issue with an immediate cost to some businesses.…”
Section: Resultsmentioning
confidence: 99%
“…Carter and LaPlant (1997) more recently analyzed how adding more information and following up to the mid‐1990s might change this categorization and found that even though more than half the states remained similarly ranked, some change was evident. This change may lead to conservative estimates if states change their amenability to diffusions of innovation over time or if states are more likely to adopt certain types of programs more than others (for an analysis of the predictors of civil liberty legislation diffusion, see Vasi and Strang 2009). Those acting as role providers in adopting and understanding screening guidelines often poorly understand recommendations (Wegwarth et al 2012), which slows the diffusion and implementation of preventive information and adds another layer of complexity.…”
Section: Discussionmentioning
confidence: 99%
“…They find that Wal-Mart was less likely to open a proposed store when protesters had successfully blocked a store opening in a nearby city. They also find that proposed stores in isolated areas were more likely to open despite protest, because there was little threat that protest would spread (see also Steil and Vasi 2014;Vasi and Strang 2009).…”
Section: Toward a Synthetic Model Of Protest Influencementioning
confidence: 99%